2020
DOI: 10.1088/1361-6528/abb506
|View full text |Cite
|
Sign up to set email alerts
|

A study of n-doping in self-catalyzed GaAsSb nanowires using GaTe dopant source and ensemble nanowire near-infrared photodetector

Abstract: This work reports a comprehensive investigation of the effect of gallium telluride (GaTe) cell temperature variation (TGaTe) on the morphological, optical, and electrical properties of doped-GaAsSb nanowires (NWs) grown by Ga-assisted molecular beam epitaxy (MBE). These studies led to an optimum doping temperature of 550 °C for the growth of tellurium (Te)-doped GaAsSb NWs with the best optoelectronic and structural properties. Te incorporation resulted in a decrease in the aspect ratio of the NWs causing an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…22 A doping concentration in the low 10 19 cm −3 range is estimated based on a reference GaAsSb material system. 22 Figure 4a represents dilute N Te-doped NWs (which shall be referred to as Te-BN hereafter) with an increased diameter of ∼215 nm, which is a strong indication of incorporation of Te, consistent with our earlier work by Ahmad et al 23 Dense NWs of 5 × 10 8 /cm 2 , comparable with BN samples, were observed with decreased axial and increased radial growth rates of 112 and 7 nm/min, respectively. A 9-fold and 4-fold increase in the emission peak intensity was observed in the RT and 4 K PL spectrum, respectively (shown in Figure 4b,c), which corroborates the increase in the free charge carrier density as a result of doping.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…22 A doping concentration in the low 10 19 cm −3 range is estimated based on a reference GaAsSb material system. 22 Figure 4a represents dilute N Te-doped NWs (which shall be referred to as Te-BN hereafter) with an increased diameter of ∼215 nm, which is a strong indication of incorporation of Te, consistent with our earlier work by Ahmad et al 23 Dense NWs of 5 × 10 8 /cm 2 , comparable with BN samples, were observed with decreased axial and increased radial growth rates of 112 and 7 nm/min, respectively. A 9-fold and 4-fold increase in the emission peak intensity was observed in the RT and 4 K PL spectrum, respectively (shown in Figure 4b,c), which corroborates the increase in the free charge carrier density as a result of doping.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…The optimization of the dopant temperature using the GaTe captive source was based on achieving the lowest ratio of dark current to photocurrent in the reference samples 7R shown elsewhere. 22 A doping concentration in the low 10 19 cm −3 range is estimated based on a reference GaAsSb material system. 22 Figure 4a represents dilute N Te-doped NWs (which shall be referred to as Te-BN hereafter) with an increased diameter of ∼215 nm, which is a strong indication of incorporation of Te, consistent with our earlier work by Ahmad et al 23 Dense NWs of 5 × 10 8 /cm 2 , comparable with BN samples, were observed with decreased axial and increased radial growth rates of 112 and 7 nm/min, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…5(b) ) at a low reverse bias of −1 V displays an S -curve behavior, characteristic of trap filling. 40 The invariant behavior of photocurrent with excitation power at a higher reverse bias of −6 V and −8 V further confirms the avalanche breakdown mechanism under illumination at −6 V, as discussed earlier in this section.…”
Section: Resultssupporting
confidence: 83%
“…From the 4 K PL spectra and the LFN measurement, the G-R noise below the corner frequency is attributed to the presence of shallow traps. 25 The biasdependent C−V characteristic of the MI NW sample in Figure 7e displays a decrease in capacitance with the bias, though remaining positive in the frequency range of 10 kHz−1 MHz, to deep level traps and/or high resistivity of the intrinsic region. 35 Similar frequency dependence is observed in other pi-n junction-based materials, namely, 4H-SiC, 35 a-Si: H, 36 Si, 37 GaN, 38 and AlGaN.…”
Section: I−v Characterization and Lfn Measurements Of Ensemble Pd The...mentioning
confidence: 98%